Enhancement of Minority Carrier Lifetime of Fe Contaminated Boron-Phosphorus Compensated p-Type SoG Silicon - Rahman, Mohammad Ziaur; Alam, Mohammad Jahangir (Photonics Letters of Poland, 2013)
To understand the role of deliberate phosphorus doping on the minority carrier lifetime of iron contaminated boron-phosphorus-compensated p-type solar grade silicon, a numerical study has been performed. This study confirmed that compensation results in a significant increase in bulk lifetime of minority carrier. The gain in carrier lifetime is predicted due to the shift in Fermi energy level, carriers screening and reduction in net equilibrium hole concentration. The bulk lifetime of minority carrier reaches its maximum for phosphorus concentration around 1015cm-3 if the boron concentrations remain fixed at 1017cm-3. Full Text: PDF References M.A. Green, Solar cells- operating principles, technology and system applications (Prentice-Hall 1986). F.E. Rougieux, D. Macdonald, A. Cuevas, "Transport properties of p-type compensated silicon at room temperature", Prog. Photovolt: Res. Appl. 19(7), 787 (2011). CrossRef F.E. Rougieux, M. Forster, D. Macdonald, A. Cuevas, B. Lim, J. Schmidt, "Recombination Activity and Impact of the Boron?Oxygen-Related Defect in Compensated N-Type Silicon", IEEE Journal of Photovoltaics 1, 54 (2011). CrossRef D. Leblanc, K. Putyera, "New resistivity/dopant density model for compensated-Si", Trans.Nonferrous Met. Soc. China 21, 1172 (2011). CrossRef S. Dubois, N. Enjalbert, J.P. Garandet, "Effects of the compensation level on the carrier lifetime of crystalline silicon", Appl. Phys. Lett. 93, 032114 (2008). CrossRef D. Macdonald, A. Cuevas, "Recombination in compensated crystalline silicon for solar cells", J. Appl. Phys. 109, 043704 (2011). CrossRef J. Veirman, S. Dubois, N. Enjalbert, J.P. Garandet, M. Lemiti, "Electronic properties of highly-doped and compensated solar-grade silicon wafers and solar cells", J. Appl. Phys. 109, 103711 (2011). CrossRef D. Macdonald, PhD Thesis (Australian National University 2001). S. Rein, Lifetime Spectroscopy (Springer 2005). A. A. Istratov, H. Hieslmair, E. R. Weber, "Iron and its complexes in silicon", Appl. Phys. A: Mater. Sci. Process. 69, 13 (1999). CrossRef W. Shockley, W. T. J Read, "Statistics of the Recombinations of Holes and Electrons", Phys. Rev. 87 (5), 835 (1952). CrossRef R.N. Hall, "Electron-Hole Recombination in Germanium", Phys. Rev. 87, 387 (1952). CrossRef A. Hangleiter, R. Hacker, "Enhancement of band-to-band Auger recombination by electron-hole correlations", Phys. Rev. Lett. 65 (2), 215 (1990). CrossRef